THE FACTORS OF STUDENTS’ AGGRESSIVENESS IN ADOLESCENCE AND YOUTH - Lezhnina, Larisa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article is devoted to the study of the actual problem of the aggressiveness of students within the walls of educational institutions, as evidenced by the growing statistics of tragic incidents in Russian schools and colleges in recent years. The subject of the research is the personal factors students’ aggressiveness from senior classes. The purpose of the research is a comparative study of personal factors, the focus of aggressiveness and the level of a conflictness of students in adolescence and youth.A theoretical basis of the study is classical approaches to the understanding of aggressiveness as a personal construct of factors that determine readiness for aggressive manifestations of negative and positive orientation. For an empirical study 158 adolescents and young people (14–17 years old) were selected.The method of organizing the investigation is an ascertaining experiment. The empirical data collection was carried out using the method of “Personal aggressiveness andconflictness” (E.P. Ilyin & P.A. Kovalev).The results obtained allowed us to give a comparative description of the personal factors of aggressiveness, its focus and students’ conflictness levels in adolescence and youth. On the basis of the assumptions put forward about interiorization and socialization as two mechanisms for the development of aggressiveness, the author identified the most important aspects of psychological and educational prevention of aggressive behavior.